Servant leadership in Malaysian higher education: a post 2020 empirical review of faculty outcomes - Janah Singh, Daljeet Singh Sedhu; Anuar, Nuramira; Mohd Nordin, Nordiana; Mohamed Jais, Ismie Roha; Mat Isa, Azman; Dass, Laura Christ; Megat Abdul Rahim, Puteri Rohani (Faculty of Information Management, 2025)
Servant leadership has gained prominence as an ethically grounded and peoplecentred leadership style in higher education. This paper reviews empirical studies published between 2020 and 2023 to examine how servant leadership has been conceptualised and applied in Malaysian higher education institutions. The review focuses on updated theoretical models, validated measurement approaches, and the effects of servant leadership on key faculty outcomes in the post-pandemic context. A structured search of Scopus, Web of Science, and Google Scholar was conducted using keywords related to servant leadership, higher education, Malaysia, and faculty outcomes. Inclusion criteria restricted the review to peer-reviewed, empirical studies within higher education, while conceptual papers and non-academic contexts were excluded. Following screening and eligibility checks, eight empirical studies were included in the synthesis. Findings demonstrate that servant leadership fosters faculty work engagement, affective commitment, job performance, innovation, and overall well-being. These outcomes are primarily explained through mediating mechanisms such as trust, leader–member exchange, job satisfaction, psychological climate, and career satisfaction. A multilevel validation of the Servant Leadership Scale (SL-28) refined the model for Malaysian academia, while longitudinal research confirmed the resilience and stability of servant leadership during the COVID-19 pandemic. The review concludes that servant leadership is both culturally congruent and practically effective in Malaysia’s high power-distance environment, where values of humility, service, and community are central. Implications are discussed for leadership development, institutional practice, and future research, including comparative ASEAN studies, integration with other leadership models, and examination of student outcomes.